Organic chemistry - Clayden, Jonathan (New York : Oxford University Press, 2012)
A first- and second-year undergraduate organic chemistry textbook, specifically geared to British and European courses and those offered in better schools in North America, this text emphasises throughout clarity and understanding.Inspiring and motivating students from the moment it published, Organic Chemistry has established itself in just one edition as the student's choice of an organic chemistry text. The second edition refines and refocuses Organic Chemistry to produce a text that is even more student-friendly, coherent, and logical in its presentation than before. Like the first, the second edition is built on three principles: An explanatory approach, through which the reader is motivated to understand the subject and not just learn the facts; A mechanistic approach, giving the reader the power to understand compounds and reactions never previously encountered; An evidence-based approach, setting out clearly how and why reactions happen as they do, giving extra depth to the reader's understanding. The authors write clearly and directly, sharing with the reader their own fascination with the subject, and leading them carefully from topic to topic. Their honest and open narrative flags pitfalls and misconceptions, guiding the reader towards a complete picture of organic chemistry and its universal themes and principles. --! From publisher's description.